Efficacy of oral zinc supplementation in management of children with acute diarrhea - نوفل سمراء; سعاد صقور; علي محمد (Latakia University Journal -Medical Sciences Series, 2022)
Background: Diarrheal disease is a mean reason for morbidity and mortality around the world, especially in developing countries. Zinc role in the treatment of acute diarrhea is still controversial. Objectives: this study aims to evaluate the role of oral zinc supplementation on the duration, frequency, consistency and hospitalization. Methods: Children of age 1to 5 years hospitalized with acute diarrhea were recruited. After the application of the inclusion and exclusion criteria, the patients were randomly allocated to two groups, which both received rehydration therapy and dietary instructions. The first group also received oral zinc ( 10 mg for children <6 months, 20 mg for children > 6 months) for 10 days. The patients were monitored daily and detailed information were added to the research form. Results: The study found significant statistical difference in favor of Zinc supplemented group, in the mean duration of diarrhea and hospitalization (2.35±0.5 VS 3.29±0.5, PV= 0.001), and frequency ( Reduced from 7.95±1.6 to 2.70±0.9 on third day of treatment for zinc group VS from 7.33±1.2 to 3.95±1.3 for control group, Pv= 0.001) and consistency (95.8% firm consistency in zinc group on fourth day of treatment VS 70.8% in control group). Conclusion: the study found beneficial effect for zinc supplementation in the treatment of acute diarrhea, by reducing its severity and duration in Syrian children.